In-office dental bleaching with violet light emitting diode: bleaching efficacy and pulpal temperature rise - Brunna Katyuscia de Almeida Guanaes; Talyta Neves Duarte; Gisele Maria Correr; Marina da Rosa Kaizer; Carla Castiglia Gonzaga (Restorative Dentistry & Endodontics)
ObjectivesThis study evaluated the bleaching efficacy of different in-office protocols associated with violet light emitting diode (V-LED), and measured the pulpal temperature rise caused by V-LED with or without gel application.Materials and MethodsBovine incisors were distributed in 4 groups (n = 10): VL – V-LED; HP – 35% hydrogen peroxide (control); HYB – hybrid protocol, V-LED applied without gel for 10 irradiation cycles followed by V-LED applied with gel for another 10 irradiation cycles; and HPVL – gel and V-LED applied for 20 irradiation cycles. Three bleaching sessions were performed with 7-day intervals. Bleaching efficacy was evaluated with ΔEab*, ΔE00 and ΔWID. Data were recorded at baseline, 7, 14, 21 and 70 days. For pulpal temperature rise, thermocouples were placed inside the pulp chamber of human incisors. To determine intrapulpal temperature, the teeth were irradiated with V-LED with or without application of bleaching gel. Color difference data were analyzed by 2-way repeated measures ANOVA and Tukey’s test. Pulpal temperature was analyzed by t-test (α = 5%).ResultsVL exhibited lower color (ΔEab* and ΔE00) and whiteness changes (ΔWID) than the other groups. HPVL presented higher color change values than HYB. HYB and HPVL showed not different ΔWID values; and HP showed the highest whiteness changes at all times. There were significant differences comparing ΔT with gel (8.9°C) and without gel application (7.2°C).ConclusionsHPLV was more efficient than HYB. The 2 protocols with VL showed similar results to control. Gel application combined with VL promoted higher pulpal temperature than to the no gel group.